2020
DOI: 10.1111/jvh.13403
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a nurse‐led enhanced monitoring, management and contact tracing intervention for chronic hepatitis B in England, 2015‐2017

Abstract: Around 200,000 people live with chronic hepatitis B in England. Despite national guidance on identification and management of cases and their close contacts, testing rates of close contacts is as low as 43% in high prevalence areas of London. Our study aimed to determine whether a nurse‐led enhanced management and contact tracing of chronically infected individuals improved testing uptake, vaccination and onward referral of close contacts. The study was conducted across Greater Manchester and East of England r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Three quarters would offer close contacts of HBV infected cases testing, and three quarters would offer close contacts hepatitis B vaccination. These proportions seem high, as many patients diagnosed with HBV and HCV are known not to be accessing secondary care – in a 2012 UK study only a third of HBV diagnosed patients were on treatment [ 45 ] and an analysis of England sentinel surveillance data showed that between 2004 and 2017 only 21% of viraemic HCV diagnosed patients had evidence of treatment [ 46 ], and baseline HBV testing of close contacts was only 34% in a 2018 UK study [ 47 ]. Our results may be due to sampling and responder bias, due to initially contacting networks who were interested in migrant health, and those who were interested being more likely to respond, as well as wishing to give socially acceptable or desirable responses.…”
Section: Discussionmentioning
confidence: 99%
“…Three quarters would offer close contacts of HBV infected cases testing, and three quarters would offer close contacts hepatitis B vaccination. These proportions seem high, as many patients diagnosed with HBV and HCV are known not to be accessing secondary care – in a 2012 UK study only a third of HBV diagnosed patients were on treatment [ 45 ] and an analysis of England sentinel surveillance data showed that between 2004 and 2017 only 21% of viraemic HCV diagnosed patients had evidence of treatment [ 46 ], and baseline HBV testing of close contacts was only 34% in a 2018 UK study [ 47 ]. Our results may be due to sampling and responder bias, due to initially contacting networks who were interested in migrant health, and those who were interested being more likely to respond, as well as wishing to give socially acceptable or desirable responses.…”
Section: Discussionmentioning
confidence: 99%
“…As the prevalence of HBV infection is low across the UK overall, there are limited data describing population characteristics and disease burden. 5 , 6 Chronic HBV (CHB) nevertheless presents a concern in certain populations, either as a result of increased prevalence and/or risk factors for the development of long-term liver disease (e.g. chronic coinfection with HIV 7 or other hepatitis viruses, 8 , 9 diabetes mellitus or metabolic syndrome, 10 , 11 alcohol abuse, 11 migrants from countries/regions with a high prevalence of HBV 12 , 13 ).…”
Section: Why Was the Cohort Set Up?mentioning
confidence: 99%
“…As the prevalence of HBV infection is low across the United Kingdom (UK) overall, there are limited data describing population characteristics and disease burden (5, 6). Chronic HBV (CHB) nevertheless presents a concern in certain populations, either as a result of increased prevalence, and/or risk factors for the development of long-term liver disease (e.g., chronic coinfection with HIV (7) or other hepatitis viruses (8, 9), diabetes mellitus or metabolic syndrome (10, 11), alcohol abuse (11), migrants from countries/regions with a high prevalence of HBV (12, 13)).…”
Section: Why Was the Cohort Set Up?mentioning
confidence: 99%
“…Leveraging existing clinical data is a cost-effective way to build a detailed description of HBV infection. Existing primary care datasets like Clinical Practice Research Datalink (CPRD) (6) do not capture HBV data well, as surveillance and treatment are largely managed in secondary care. During the last decade, large amounts of routinely-collected clinical data have been accumulated in electronic patient record (EPR) systems in the UK’s unified secondary care services.…”
Section: Why Was the Cohort Set Up?mentioning
confidence: 99%
See 1 more Smart Citation